Dimensional changes of upper airway after slow vs rapid miniscrew-supported maxillary expansion in adolescents: a cone-beam computed tomography study - Yomna M. Yacout; Nadia M. El-Harouni; Ahmed M. Madian (BMC, 2022)
Abstract Background To date, the effects of different activation rates of miniscrew-supported expanders on the airway have not been compared. Hence, the purpose of this retrospective study was to evaluate and compare the effects of slow and rapid miniscrew-supported maxillary expansion on the upper airway dimensions using cone-beam computed tomography (CBCT). Methods Data of 20 patients (Age 12 to 16 years old) treated using miniscrew-supported expanders at the Faculty of Dentistry, Alexandria University was collected. The patients were equally divided into two groups according to the activation protocol; slow maxillary expansion (SME): activation once every other day, and rapid maxillary expansion (RME): activation twice daily. CBCT scans obtained pre-expansion and 5 months post-expansion were used to evaluate the changes in the upper airway dimensions. Comparisons between the two time points within each group were done using paired samples t-test. SME and RME groups were compared using independent samples t-test. Significance level was set at p < 0.05. Results Both groups showed a significant increase in anterior, middle, and posterior nasal cavity width. SME resulted in significantly greater increase of the anterior nasal cavity width than RME (Mean difference between the groups, 2.64 mm; 95% CI, 0.83, 4.45; p = 0.007). The dimensions of the retropalatal and retroglossal airways did not change significantly in either group. Both groups resulted in a significant increase of maxillary width, palatal width, and inter-molar width. RME showed a significantly larger increase of inter-molar width than SME (Mean difference between the groups, − 2.44 mm; 95% CI, − 3.88, − 1.00; p = 0.002). Conclusions The use of either a slow or rapid activation protocol is effective in expanding the nasomaxillary complex, with greater expansion achieved in the anterior section of the nasal cavity using the slow rate. However, the expander design employed in the current study does not affect the dimensions of the retropalatal or retroglossal airways.